The Handbook for the New Art and Science of Teaching : (Your Guide to the Marzano Framework for Competency-Based Education and Teaching Methods). - Marzano, Robert J. (New Art and Science of Teaching Ser., 2018)
In this expanded volume, Marzano identifies ten design areas within three categories of teaching - (1) feedback, (2) content, and (3) context - that form a road map for K-12 teachers' lesson and unit planning. These design areas include: providing and communicating clear learning goals (1); using assessments (1); conducting direct instruction lessons (2); conducting practicing and deepening lessons (2); conducting knowledge application lessons (2); using strategies that appear in all types of lessons (2); using engagement strategies (3); implementing rules and procedures (3); building relationships (3); and communicating high expectations (3). Within these ten design areas, Marzano explores forty-three categories of instructional strategies that contain more than 330 specific classroom strategies educators can implement for optimal student learning. Each chapter provides guidance for planning changes and highlights current education practices to put the strategies in place. Readers will: explore more than 330 classroom strategies; discover specific mental states and processes learners need in order to reach peak academic success; gain a general framework to help in planning what classroom strategies to use to foster specific student learning outcomes; analyze the behavioural evidence that proves strategies are producing the desired effects; and study the state of the modern standards movement and what changes are necessary in K-12 education for it to reach the next level of effectiveness. -- Provided by publisher.